2021
DOI: 10.5812/hmj.106093
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Phenolic Compounds Profile of Pistachio Skins (Pistacia vera L., cultivars Kallehghuchi and Ohadi)

Abstract: Background: Pistachio, with the scientific name Pistacia vera L., a native plant in Asia, is a member of the Anacardiaceae family. Pistachio nuts and skins are known as a rich source of phenolic compounds with antioxidant, anti-inflammatory, and antimicrobial properties. Objectives: In the current study, the industrial production of phenolic compounds with antioxidant activity was investigated because of the high mass production of pistachio skin in Iran. Methods: The extraction of two pistachio cultivars, nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Azadedel et al 50 have reported the antioxidant properties of pistachio hull extracts of two cultivars, Kallehghuchi and Ohadi, with the addition of four solvents (acetone, methanol, ethanol, and water) with two methods (ultrasound and soaking). In their study, all pistachio hull extracts showed powerful antioxidant properties, so in the DPPH method, the antioxidant properties of the extracts were much higher than the gallic acid and ascorbic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Azadedel et al 50 have reported the antioxidant properties of pistachio hull extracts of two cultivars, Kallehghuchi and Ohadi, with the addition of four solvents (acetone, methanol, ethanol, and water) with two methods (ultrasound and soaking). In their study, all pistachio hull extracts showed powerful antioxidant properties, so in the DPPH method, the antioxidant properties of the extracts were much higher than the gallic acid and ascorbic acid.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that RPH extract improved memory impairment due to diabetes mellitus in rats. Phenolic compounds were found in the pistachio, with antioxidant, anti-inflammatory, and antimicrobial effects (Azadedel, Hanachi, & Saboora, 2017). In epidemiological studies, it was proven that phenolic flavonoids, as antioxidants in pistachio red peal, have improved memory performance in older rats (Mozdastan, Ebrahimzadeh, & Khalili, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenol compounds are plant metabolites with free radical scavenging properties. There is a linear ratio between the total phenolic content of the plant and its antioxidant potential [58]. Antioxidant activity values of H. excedens mushroom extract and synthesized AgNPs/He were determined using the DPPH method and IC 50 was found as 47.98 and 22.93 mg/ml, respectively (Table 2).…”
Section: Bioactive Componentsmentioning
confidence: 99%